KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PINRANG - Muin, Muhammad Anwar (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
This research is quantitative descriptive research and this research aims to find out the contribution of local taxes to local Indigenous income, and the inhibitory factors faced by the government in reducing local taxes and efforts made by the district government in the management of local taxes. The data collection techniques used in this study are observation, interview, and documentation. The data analysis techniques in this study use contribution analysis and descriptive analysis. The results of this study are known that in 2014 to 2018, the largest contribution of local tax to the original income of Pinrang district occurred in 2017 which is 20.79% and categorized fairly, but thus the contribution of local tax to the local native income in the last 5 years is still relatively small which is below 20% of the contribution criteria set by the team of the Research and Development Agency of the Ministry of Home Affairs UGM. Local financial institutions still have a factor in increasing local taxes, one of which is that taxpayer awareness is still low, but local governments also have efforts underway to overcome all obstacles faced including providing understanding by socializing to taxpayers to meet the obligation to pay taxes in accordance with applicable local regulations.